Editorial: Politicization of EU Trade Policy Across Time and Space - De Bièvre, Dirk (2020)
This editorial provides an introduction to the thematic issue “Politicization of EU Trade Policy Across Time and Space.” The academic editors place the issue in the context of the current literature, introduce the contributions, and discuss how the articles, individually and jointly, add to the state of the art.